Whole-exome sequencing in individuals with multiple cardiovascular risk factors and normal coronary arteries. Issue 4 (June 2016) - Abramowitz, Yigal; Roth, Arie; Keren, Gad; Isakov, Ofer; Shomron, Noam; Laitman, Yael; Weissglas-Volkov, Daphna; Arbel, Yaron; Banai, Shmuel; Finkelstein, Ariel; Friedman, Eitan
Abstract : Objectives: Most studies on the genes involved in coronary artery disease (CAD) targeted individuals with angiographically or clinically proven CAD. Focusing on high-risk individuals with normal coronary arteries (NCA) may offer novel insights into the pathogenesis of CAD. We aimed to identify genes putatively protective for development of CAD. Methods: Pooled whole-exome sequencing (WES) was performed on 17 patients with multiple cardiovascular risk factors and NCA and on 17 controls with multivessel CAD. Rare NCA-unique sequence variants were subsequently individually validated using the Fluidigm platform in 100 additional CAD controls and 100 general population controls. Results: In total, 555 100 variants were detected in at least one WES pool in the study group and in none of the control WES pools. For second phase validation, we focused on rare, nonsynonymous variants, resulting in a total of 144 variants in 40 genes, of which 96 were selected for subsequent genotyping. Validation phase genotyping resulted in 19 variants in 16 genes that were found in the NCA group and in none of the CAD controls. The SPTBN5, NID2, and ADAMTSL4 genes harbored sequence variants in more than one CAD-protected patient and none of the 117 CAD controls. Conclusion: Applying WES technology and focusing on individuals seemingly protected from developing CAD successfully identified 19 variants that may offer protection from CAD by undetermined mechanisms. Studying the genetics of high-risk individuals apparently protected from CAD may provide novel insights into the pathogenesis of CAD. Abstract : Supplemental Digital Content is available in the text.